MEMUNGUT PPN ATAU TIDAK KETIKA BENDAHARA DESA BERTRANSAKSI DENGAN PENGUSAHA NON PKP - Mohammad Djufri (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2019)
There are differences of opinion regarding the collected of VAT when Villlage Government Treasurers - who now changed his name to Head of Financial Affairs - deals with Non Taxable Entrepreneur partners with practices. The opinion states that there is no collected VAT by the Head of Financial Affairs whenever deals with Non Taxable Entrepreneur partners. There are two reasons how to collected VAT by Head of Financial Affairs. Firstly, status of Taxable Entrepreneur is a condition for tax payable mechanism and secondly, must be a tax invoice for each transaction. Practically, the Village Government Treasurer collected VAT on each transaction with Non Taxable Entrepreneur partners. This paper aims to clarify this issue through normative research. The result of this paper, that two reasons of collected VAT (status of Taxable Entrepreneur and the existence of tax invoices) are inappropriate. The most appropriate is set by the decree of the Director General of Taxes No. Kep-382 / PJ. / 2002, which clearly states that the VAT collector does not need to collect VAT on delivery of Taxable Goods or Taxable service by Non Taxable Entrepreneur. The rule can be a reference for the Head of Financial Affairs not to collect VAT to Non Taxable Entrepreneur partners. In fact, the rule can be interpreted differently because there are special rules (provisio) in the VAT Act and the issuance of this rule does not comply with the principle of lex superior derogat legi inferior. To provide legal certainty that is clear and firm and does not contain double meaning or provide an opportunity to be interpreted, new regulations are required at the lowest level of the Ministry of Finance Regulation as mandated by the VAT Law, and in that rule to be returned to special rule as stated in Article 16A.